Use of Discrete Fiber in Rigid Road Pavement (International Journal of Innovative Research in Engineering & Management, 2023)
Concrete roads are very common and can  provide safe and smooth traffic. Thanks to the use of concrete  on the roads it has become a very good quality of life and  low maintenance. However, concrete roads may be cracked,  cracked, and the concrete weakened and malfunctioned. To  alleviate these problems Fiberglass installation can provide  significant concrete advantages. The study “Use of Separated  Ropes in Solid Roadways” was conducted to improve the  quality of concrete roads. In this study the fiber used was  polypropylene fiber and polyester fiber. The concrete mix  used is M25. In just one example, concrete mixes were tested  for compressive strength, flexural strength and strength split  strength. In the second specimen 1.6% polypropylene fiber  was added to the concrete mixture and tested in three similar  tests. In the third sample 0.4% of polyester fiber is applied to  the concrete mix and tested for compressive strength,  flexural strength and tensile strength is divided. In the fourth  specimen both 1.6% polypropylene fiber and 0.4% polyester  fiber were mixed with concrete mix and three tests were  tested. Road transport is undoubtedly the nation's way of life and its  development is of paramount importance. Small traditional  paraffin and its maintenance requirements and rehabilitation  performance indicate the size of the concrete concrete areas.  There are several advantages of cement concrete for small  stone concrete. This paper focuses on the POLYMER FIBER  REINFORED CONCRETE PAVEMENTS, a recent  development in the field of reinforced concrete design.  Comparative studies of these conventional concrete routes  were performed using Polypropylene fiber waste as fiber  reinforcement
Keywords: Concrete pavement; polypropylene fiber; polyester fibe; Ccompressive strength; Flexural strength; split tensile strength